Degree of implementation of occupational Safety and health management systems (OSHMS), in the metalworking industries of the south-central region of Caldas – Colombia (2016)
(Eng) Colombia has some mandatory regulations for all companies, regardless their business area or their economic activity respect to Occupational Safety and Health. In this project, it was reported the results of the degree of implementation of the Occupational Safety and Health Management Systems (OSHMS) with regard to the level of obligation required by law. The data was collected from Social Security Institute survey-type instrument adapted by Autonomous University of Manizales experts; and validated through pilot testing. Throughout a convenience sampling, 26 companies in the metal/ mechanical industry of the South-central region of Caldas were evaluated. Small companies showed major gaps compared to the medium and large businesses in term of the degree of implementation of the Occupational Safety and Health Management Systems (OSHMS). Features related to compliance with the requirements of appointing staff, function assigning of the Joint Committee on Occupational safety and health, well established occupational safety and health policies, well defined spaces for first aid care; and high qualified staff to design, implement and maintain the system.